A Comparative Study of Population Health in the United States and Canada during the Neoliberal Era, 1980–2008. (April 2013) - Siddiqi, Arjumand; Kawachi, Ichiro; Keating, Daniel P.; Hertzman, Clyde
This article draws on the vast evidence that suggests, on one hand, that socioeconomic inequalities in health are present in every society in which they have been measured and, on the other hand, that the size of inequalities varies substantially across societies. We conduct a comparative case study of the United States and Canada to explore the role of neoliberalism as a force that has created inequalities in socioeconomic resources (and thus in health) in both societies and the roles of other societal forces (political, economic, and social) that have provided a buffer, thereby lessening socioeconomic inequalities or their effects on health. Our findings suggest that, from 1980 to 2008, while both the United States and Canada underwent significant neoliberal reforms, Canada showed more resilience in terms of health inequalities as a result of differences in: ( a ) the degree of income inequality, itself resulting from differences in features of the labor market and tax and transfer policies, ( b ) equality in the provision of social goods such as health care and education, and ( c ) the extent of social cohesiveness across race/ethnic- and class-based groups. Our study suggests that further attention must be given to both causes and buffers of health inequalities.